Nutrient Patterns and Risk of Polycystic Ovary Syndrome - Gh Eslamian; A Hekmatdoost (JRI, 2019)
Background: There are limited data on the role of nutrient patterns in development of polycystic ovary syndrome (PCOS). The aim of the study is to document the relationship between nutrient patterns and PCOS. Methods: In this study, 281 incident PCOS women and 472 controls were interviewed through the endocrine clinics between February 2013 and March 2015 in Tehran, Iran. Usual dietary intakes were obtained using a validated semi-quantitative food frequency questionnaire. Factor analysis was conducted on the basis of 32 nutrients. Unconditional logistic regression was performed to ascertain odds ratios. The p<0.05 was considered for significance level. Results: In principal component analysis two nutrient patterns emerged. Factor 1 had high loadings for riboflavin, niacin, pyridoxine, thiamin, magnesium, pantothenic acid, cobalamin, vitamin C, folate, vitamin D, total fiber, selenium, phosphorus, vitamin E, manganese, vitamin K, monounsaturated fatty acids, polyunsaturated fatty acids, potassium and vegetable protein. Factor 2 characterized by high loadings for carbohydrate, animal protein, fat, cholesterol, saturated fatty acid, sodium, biotin, copper, iron, fluoride, zinc, and calcium. After adjusting for potential confounders, the risk of PCOS was significantly higher in the highest tertile of factor 2 (OR: 2.38, 95% CI: 1.69-3.21). Conversely, being in the highest tertile of factor 1 was associated with a lower risk of PCOS (OR: 0.48, 95% CI: 0.21-0.82).  Conclusion: Our results provide a possible new insight into the interactions between nutrient intakes and PCOS.